Analysis of Environmental Literacy of Students (Behavioral Dimension) from a Humanistic Perspective - Mellyzar, Mellyzar; Riksa Yustiana, Yusi; Nahadi, Nahadi; Rahmi, Ayu; Virijai, Febrian (Indonesian Journal of Mathematics and Natural Science Education, 2024)
Environmental literacy is crucial in preparing individuals to face global challenges related to environmental issues such as climate change and pollution. This study aims to explore the behavioral dimension of students' environmental literacy and analyze the relevance of integrating humanistic values to strengthen it. The research employed a descriptive approach involving 55 students from the Chemistry Education Program at a state university in Aceh Province. Data were collected through a questionnaire measuring three behavioral indicators: involvement in responsible environmental behavior, environmental action strategies and skills, and intention to act. The results showed that students had a good level of engagement in environmental behaviors, although there were challenges in adopting certain habits, such as reducing single-use plastic. Furthermore, students demonstrated a strong intention to engage in pro-environmental actions, particularly in changing harmful behaviors and participating in sustainability activities. This study concludes that humanistic-based education can strengthen students' environmental literacy by emphasizing the importance of reflection, moral responsibility, and experience-based learning in creating agents of change for environmental sustainability.